Tectônica do habitar moderno: estudo em João Pessoa e Campina Grande, Paraíba (1950-1960) - Diniz, Diêgo Claudino de Sousa (2022)
This paper aims to analyze the tectonic nexus of modern single-family residential architecture in Paraíba, particularly, examples built in João Pessoa and Campina Grande in the 1950s and 1960s, exploring the constructive poetics expressed in this building type. This research is justified as it contributes to the historiography of modern architecture produced in northeastern Brazil, increases knowledge about the singularities of the technical and constructive knowledge present in the buildings, and contributes to the documentation of significant and still existing examples of modern heritage. The methodological procedure starts from the bibliographical review, followed by data collection, selection of the works and application of the tectonic analytical parameters proposed by Rocha (2012), which focuses on the relations of site, resistant structure and sealing elements with the formal architectural structure. Faced with a vast number of residences, those that had sufficient design material and that made it possible to conduct a visit for construction recognition were chosen, namely, the Cassiano Ribeiro Coutinho residence (1955-1958), the Joaquim Augusto Residence (1956-1958), the José Barbosa Maia residence (1962-1964), and the Heleno Sabino residence (1962-1963). The results show that there is a tectonic diversity present with greater emphasis on the sealing elements, as well as on the architectural party resulting from the embankment work as fundamental to the architectural expressiveness, while the potential of the structural form built unanimously in reinforced concrete is not always evident. Thus, a present duality in architectural form is perceived, referring to the dyads open and closed, light and heavy, transparent and opaque, present in modern architectural culture.